Spokane Committee selecting site for Spokane Building, Alaska-Yukon-Pacific Exposition, Seattle, Washington, March 27, 1908 - Nowell, Frank H., 1864-1950 (1908)
On verso of image: Spokane Committee selecting site for Spokane Bldg. Left. I.R. Nadeau Caption on image: x18 PH Coll 727.34 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number